Effectiveness of current and alternative procurement modalities: An evaluation of the effectiveness of current and potential alternative grain procurement modalities, and development of a framework for stock turnover - Rashid, Shahidur; Mustafa, Shoumi; Kabir, Razin; Shaima, Nabila Afrin (International Food Policy Research Institute, 2024)
This report has been prepared as one of the deliverables of the Bangladesh Integrated Food Policy Research Program (BIFPRP) implemented by the Ministry of Food, Government of Bangladesh under a World Investment for Modernizing Food Storages Facilities in the country. The key arguments and recommendations drawn up for the report are based on both quantitative and qualitative data. Food and agricultural policies have historically played a crucial role in triggering growth in many developing countries. While there were debates, public procurement and distribution of food are widely accepted as a “second best” solutions for countries characterized by markets and institutional failures. However, Bangladesh has done remarkably well in adjusting to changing realities and the country is now widely recognized for its agricultural policy reforms. But there is still room for further improvement and efficiency gains for which two broad sets of recommendation can be considered: 1) Pricing and procurement targets - Pricing in Bangladesh continues to be based on the average cost of production but with the application of satellite imageries, app-based small area estimation, the procurement price estimates can be improved substantially. Also, the current procurement target determination formula misses out on some key aspects of production, marketing, and macroeconomic parameters. The quota for each upazila is based on total production and milling capacities but it also needs to consider the net surplus to calculate how much could be procured in each Upazilas. 2) Alternative procurement modalities a) The report recommends changing this modality to Delivered to Destination Warehouse (DDW) through the open tendering method and undertaking pilots and learning from experiences to enhance efficiency can be important. b) Linking smallholders to markets through product aggregation has received renewed attention globally. Available data suggests that Bangladesh’s public procurement has thus far not managed to effectively integrate small farmers to its procurement system. To scale up nationally, we believe that more innovation in technology and a new institutional set up will be necessary. c) Implementing Delivered Duty Paid Modality on a pilot basis where the seller assumes all responsibilities and costs for delivering the goods to the named place of destination. d) Piloting Deficiency Payment Method as an effective method to provide both income and price to farmers of a wide range of agricultural commodities. Two key instruments of implementing this method would be Marketing Assistance Loan (MAL) and the Loan Deficiency Payment (LDP), which are tools available to the farmers. A recent report by the NITI Aayog of India also makes a strong case for this procurement modality and we also argue in favor of undertaking this pilot.